The role of autophagy in colorectal cancer: Impact on pathogenesis and implications in therapy - Mahgoub, Eglal; Taneera, Jalal; Sulaiman, Nabil; Saber-Ayad, Maha (Frontiers in Medicine, 2022)
Colorectal cancer (CRC) is considered as a global major a leading cause of cancer death. worldwide. Surgical resection is the main line of treatment; however, chemo-, radiotherapy and other adjuvant agents are crucial to achieve good outcomes. Favorable response to immunotherapy occurs only in a specific subpopulation of patients, namely the microsatellite instability-high (MSI-H). The tumor microenvironment (TME) is a well-recognized key player in CRC progression, yet the processes linking the cancer cells to its TME are not fully delineated. Autophagy is one of such processes, with has a a controversial role in the pathogenesis initiation and progression of CRC, with its intricate links to many pathological factors and processes. Autophagy may apparently play conflicting roles in carcinogenesis, but the precise mechanisms determining the overall direction of the process seem to depend on the context. Additionally, it has been established that autophagy has a remarkable effect on the endothelial cells in the TME, the key substrate for angiogenesis that supports tumor metastasis. Favorable response to immunotherapy occurs only in a specific subpopulation of CRC patients, namely the microsatellite instability-high (MSI-H). In view of such the current limitations of immunotherapy in CRC, to the MSI-H tumors, modulation of autophagy represents a potential adjuvant strategy to enhance the effect of those relatively safe agents on wider CRC molecular subtypes. In this review, we discussed the molecular control of autophagy in CRC and how autophagy affects different processes and mechanisms that shape the TME. We explored how autophagy contributes to CRC initiation and progression, and how it interacts with tumor immunity, hypoxia, and oxidative stress. The crosstalk between autophagy and the TME in CRC was extensively dissected. Finally, we reported the clinical efforts and challenges in combining autophagy modulators with various cancer-targeted agents to improve CRC patients’ survival and restrain cancer growth.